2014
DOI: 10.1074/mcp.m113.027813
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Identified Multiple Short-lived Members of the Central Proteome as the Direct Targets of the Addicted Oncogenes in Cancer Cells

Abstract: Oncogene addiction is an unexplained phenomenon in the area of cancer targeted therapy. In this study, we have tested a hypothesis that rapid apoptotic response of cancer cells following acute inhibition of the addicted oncogenes is due to loss of multiple short‐lived proteins whose activity normally maintain cell survival by blocking caspase activation directly or indirectly. It was shown that rapid apoptotic response or acute apoptosis could be induced in both A431 and MiaPaCa‐2 cells, and quick down‐regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…41 19S lid component PSMD11 was among the top down-regulated proteins after PI3K inhibition in lung and pancreatic cancer cells in another proteomic study. 42 Consistent with the association of low cycling and low proteasome activity, normal human embryonic stem cells (hESCs), which, in contrast to CSC counterparts, have a high cycling activity during developmental organogenesis, possess a high proteasome activity. 43 This is an important distinction to emphasize with pathogenic and possible therapeutic implications.…”
Section: Proteasome Activity In Cancer and Cscsmentioning
confidence: 86%
See 1 more Smart Citation
“…41 19S lid component PSMD11 was among the top down-regulated proteins after PI3K inhibition in lung and pancreatic cancer cells in another proteomic study. 42 Consistent with the association of low cycling and low proteasome activity, normal human embryonic stem cells (hESCs), which, in contrast to CSC counterparts, have a high cycling activity during developmental organogenesis, possess a high proteasome activity. 43 This is an important distinction to emphasize with pathogenic and possible therapeutic implications.…”
Section: Proteasome Activity In Cancer and Cscsmentioning
confidence: 86%
“…41 19S lid component PSMD11 was among the top down-regulated proteins after PI3K inhibition in lung and pancreatic cancer cells in another proteomic study. 42…”
Section: Proteasome Activity In Cancer and Cscsmentioning
confidence: 99%
“…PSMD11 was overexpressed in breast cancer tissue, and this may be associated with specific biological processes and pathological types of breast cancer (65). PSMD11 is a short-lived protein, and knockdown of PSMD11 via RNA interference partially resulted in the occurrence of acute apoptosis in pancreatic cancer cells (66). It was identified that high expression of PSMD3 and PSMD11 was associated with poor overall survival in patients with melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…After 4 hr, the expression of PSMD11 all increased to a higher level (about 2.1‐folds for MiaPaCa‐2 and 2.5‐folds for PANC‐1 cells) compared to normal control, indicating that HHT could also not inhibit induction of protein synthesis of PSMD11 in pancreatic cancer cells. For PSMD11 had been demonstrated to be an acute apoptosis inhibitor in our previous studies, these data suggested that selectively induction of protein synthesis of PSMD11 following treatment with protein synthesis inhibitors might be one of the common and important mechanism by which pancreatic cancer cells could avoid quick apoptosis.…”
Section: Resultsmentioning
confidence: 67%